PThe Role Of State Administrative Courts In Ensuring Legal Protection For Indonesian Citizens - Darwin Wibowo Sihombing; Mirale Harahap (AT-TAFAHUM: Journal of Law, 2022)
The State Administrative Court (PTUN) plays a strategic role in ensuring legal protection for citizens from detrimental government administrative actions. As one of the pillars of the rule of law, the PTUN functions to supervise, adjudicate, and resolve disputes between the public and state administrative bodies or officials in order to create a balance of fair legal relations. This study aims to analyze the role of the PTUN in providing legal protection and identify obstacles in its implementation. The method used is normative legal research with a statutory and conceptual approach. The results show that the PTUN plays a significant role in upholding administrative justice, preventing abuse of authority, and providing legal certainty for the public. However, the effectiveness of the legal protection provided still faces various obstacles, such as low public legal awareness and less than optimal implementation of court decisions. Therefore, institutional strengthening, increased legal socialization, and government commitment to implementing PTUN decisions are needed so that legal protection for citizens can be realized optimally.